Where is the strength of evidence? A review of infection prevention and control guidelines. Issue 2 (June 2020) - Mitchell, B.G.; Fasugba, O.; Russo, P.L.
Summary: An important aspect of safety and quality in healthcare is the implementation of infection prevention and control guidelines. However, little is known regarding the strength of evidence on which recommendations for such guidelines are based. This study aimed to describe the strength of recommendations of infection prevention and control guidelines published in the last 10 years. For this review, the websites of government and professional organizations for national and international infection prevention and control clinical guidelines were purposively searched. The search was limited to publications between January 2009 and April 2019, and those with a formal grading system were used to determine the strength of the evidence underpinning the recommendations. Recommendations from guidelines were categorized into 21 infection control categories. A descriptive synthesis of the data was undertaken. A total of 31 guidelines comprising 1855 recommendations were included. Guidelines were mainly developed in the USA ( N  = 11, 35.5%) and Canada ( N  = 9, 29.0%). Most guidelines used the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach ( N  = 6, 19.4%. The majority of the guidelines contained recommendations categorized under the themes of devices ( N  = 316, 16.9%) and transmission-based precautions ( N  = 315, 16.8%). Most recommendations ( N  = 769, 41.5%) were graded as using evidence from descriptive studies, expert opinion and low-quality evidence. There are a vast number of infection prevention and control guidelines developed by national and international government or professional organizations, many without a strong evidence base. This presents multiple research opportunities that should prioritize common prevention activities that currently have a low evidence base.